The choice of method and results of surgical treatment for rectal fistulas - A. O. Nykonenko; G. І. Okhrimenko; M. G. Golovko; V. A. Grushka; S. O. Vilkhovoi; A. S. Aleksandrov (Клінічна хірургія)
Objective. To study the immediate and remote results of treatment in patients with rectal fistulas, in whom Gabriel operation, Maslyak operation, and the ligature method were applied, as well as to create optimal indications to every kind of surgical intervention.